Divergent metabolic adjustments in nodules are indispensable for efficient N2 fixation of soybean under phosphate stress. (December 2019) - Sulieman, Saad; Kusano, Miyako; Ha, Chien Van; Watanabe, Yasuko; Abdalla, Muna Ali; Abdelrahman, Mostafa; Kobayashi, Makoto; Saito, Kazuki; Mühling, Karl H.; Tran, Lam-Son Phan
Highlights: Soybean acclimation to Pi scarcity is markedly influenced by its rhizobial partner. Soybean changes its nodule N metabolism and export to cope with Pi stress. Utilization of the overall carbon budget defines the nodule sensitivity to Pi stress. Fatty acids and phytosterols are essential for efficient symbiosis under Pi stress. Secondary metabolism is involved in nodule acclimation to Pi deficiency. Abstract: The main objective of the present study was to characterize the symbiotic N2 fixation (SNF) capacity and to elucidate the underlying mechanisms for low-Pi acclimation in soybean plants grown in association with two Bradyrhizobium diazoefficiens strains which differ in SNF capacity (USDA110 vs. CB1809). In comparison with the USDA110–soybean, the CB1809–soybean association revealed a greater SNF capacity in response to Pi starvation, as evidenced by relative higher plant growth and higher expression levels of the nifHDK genes. This enhanced Pi acclimation was partially related to the efficient utilization to the overall carbon (C) budget of symbiosis in the CB1809-induced nodules compared with that of the USDA110-induced nodules under low-Pi provision. In contrast, the USDA110-induced nodules favored other metabolic acclimation mechanisms that expend substantial C cost, and consequently cause negative implications on nodule C expenditure during low-Pi conditions. Fatty acids, phytosterols and secondary metabolites are characterized among the metabolic pathways involved in nodule acclimation under Pi starvation. While USDA110–soybean association performed better under Pi sufficiency, it is very likely that the CB1809–soybean association is better acclimatized to cope with Pi deficiency owing to the more effective functional plasticity and lower C cost associated with these nodular metabolic arrangements.